Service User Involvement in Mental Health Practitioner Education in Ireland - McCann, Edward; Maguire, Gerry; Watts, Mike; Creaner, Mary; Agnes, Higgins; Rani, Shobha; Alexander, Jane (My University, 2011)
In recent years, there is an ever- increasing call to involve people who use mental health services in the development, delivery and evaluation of education programmes. Within Ireland, there is very little evidence of the degree of service user involvement in the educational preparation of mental health practitioners. This paper presents the findings on service user involvement in the education and training of professionals working in mental health services in Ireland. Findings from this study indicate that in the vast majority of courses curricula are planned and delivered without consultation or input from service users. Currently the scope of service user involvement is on teaching, with little involvement in curriculum development, student assessment and student selec- tion. However, there is evidence that this is changing, with many respondents indicating an eagerness to move this agenda forward.
Keywords: service users; education; mental health; involvement; service user involvement; multidisciplinary education